The Gifts of Erasmus: 2021 Margaret Mann Phillips Lecture. - Barker, William (Erasmus Studies (2451-9723), 2023)
The article is a short introduction to the life-long gift-practice of Erasmus—the gifts he received, the gifts he gave, and the symbolic and moral meaning of the gift cycle of reception, gratitude, and reciprocation that pertained to a wide range of exchanges—from small objects to casks of wine to large gifts of money. His book dedications also belonged to that same gift cycle. His management of gifts was driven in part by necessity, as he needed funds and sometimes protection in order to pursue his studies and writing outside the normal framework of institutional structures. Gifts were a sign of his capacity to flourish within the community of friends (and donors) that he was able to draw around himself.